Los corresponsales peruanos en la Guerra del Pacífico - Gargurevich, Juan (2015)
Little significance has been given to the important role played by journalism during the previous trial to the Chilean’s War Declaratory against Peru and Bolivia. In the same way to the journalists, the war stringer who were sent by the newspapers with the aim of covering warlike events including naval procedures. Among them, there were four journalists who kept their readers updated with the most patriotic and shocking columns. For instance, we must never forget names like Del Campo, Neto, Reyes and Horta.